Studies on the Electrical and Optical Properties of High Quality Cuprous Oxide Material Produced by Thermal Oxidation for Solar Cell Applications - S. M. Kurawa; A. O. Musa; Y. I. Bunkure; T. H. Darma; R. S. Getso; S. Shafie; S. Faruk (Current Overview on Science and Technology Research Vol. 3, 2022)
Investigations were done into the structural, morphological, and opto-electrical properties of cuprous oxide. In order to create high-quality cuprous oxide materials, copper foil was thermally oxidised. This method worked well to create cuprous oxide films with a high degree of purity and big grain sizes. The X-ray diffraction (XRD) revealed that the films have a cubic structure with preferred (111) orientation at 2\(θ\) angle of 36.51o. Scanning electron microscope (SEM) micrograph revealed that the material is rough on a micro scale with an average grain size of 0.68\(μ\)m. The optical band gap energy for Cu2O was estimated to be 2.11eV. The low electrical resistivity of 2.59 x 102\(Ω\)cm was calculated for Cu2O. The maximum power was found to be 1.84x10-4mWcm-2 for the cell without current collection grids while 2.61x10-4mWcm-2 was found to be the maximum power for the cell with current collection grid at constant illumination of 60Wm-2. The efficiencies and fill factors for the cells with and without current collection grids were found to be 3.07x10-4 % and 0.49, 4.35x10-4 % and 0.58 respectively. The above findings makes cuprous oxide a good material for photovoltaic applications.